Kekerasan dalam Rumah Tangga dalam Perspektif Hukum Positif dan Hukum Islam di Indonesia - Achmad Rasyid Ridha; Qadir Gassing; Abd. Rahman R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Domestic violence (DV) is a social and legal issue that remains a serious problem in Indonesia. This phenomenon not only impacts victims physically but also causes psychological trauma, social loss, and disruption to family stability. This study aims to analyze the concept of domestic violence, its forms, causal factors, and efforts to address it from the perspective of positive law and Islamic law. The results indicate that domestic violence is influenced by unequal power relations, patriarchal culture, economic pressure, and a weak understanding of the values of justice in religious teachings. Therefore, an integrative legal and religious approach is needed to prevent and address domestic violence